Relação entre o nível de maturidade em gerenciamento de projetos e o desempenho das políticas públicas municipais: um estudo da percepção dos secretários de educação e saúde dos municípios do Estado do Paraná - Trevisan, Rosel Garcez (2013)
Due to the current social demands, citizens started to question the public management actions towards the existing social gaps. In the present context, public policies need to be more effective and efficient. As projects are integral parts to determine how public policies are implemented, nowadays organizations are increasingly seeking efficiency when managing projects because they are aware that it will improve their performance. The present study aims at identifying the relationship between the maturity level of the Health and Education Municipal Departments and the municipal public policy performance of these areas in the state of Paraná. From 1990 on, models of project management maturity assessment emerged as a result of the increasing popularization of such practice and project importance within organizations. Our research used the Project Management Maturity Model (MMGP) and we identified a positive relationship between project management maturity level and municipal performance in the health and education areas through a field research. This positive relationship implies that the higher the project management maturity level is, the better the municipal performance will be. Thus, we show that efficient and effective project management provides a better organizational performance.